Exposé : peryodismong pampelikula sa Pilipinas = movie reporting in the Philippines - Villasanta, Julianito (b, 2007)
Motion picture and celebrities in Philippine journalism.
Includes bibliographical references (p. 383-394) and index.
MC
In Tagalog.
Keywords: Motion picture journalism -- Philippines; Celebrities -- Philippines